2022
DOI: 10.1021/acsbiomaterials.1c01521
|View full text |Cite
|
Sign up to set email alerts
|

Post-Cross-Linking of Collagen Hydrogels by Carboxymethylated Polyrotaxanes for Simultaneously Improving Mechanical Strength and Cell Proliferation

Abstract: To improve the mechanical properties of collagen hydrogels, which are widely utilized as biomaterials, post-cross-linking of collagen hydrogels was performed using polyrotaxane (PRX) as a cross-linker. Herein, carboxymethyl group-modified PRXs (CMPRs) composed of carboxymethylated α-cyclodextrins (α-CDs) threaded along poly­(ethylene glycol) (PEG) capped with bulky stoppers were used to cross-link via reaction with the amino groups in the collagen. Four series of CMPRs with different α-CD threading ratios and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Both the fracture stress and strain were enhanced by increasing the molecular weight of the PRs from 20,000 to 100,000, which indicated that the increased effective range of αCD resulting from the higher molecular weight significantly affected the gel mechanical properties. A similar effect of molecular weight was reported for atelocollagen hydrogels post-crosslinked with carboxymethyl PRs [58]. Note that molecular weight exerted a stronger effect on the fracture stress and strain than coverage ratio in the previous studies.…”
Section: Tensile Testing Of Pratssupporting
confidence: 80%
“…Both the fracture stress and strain were enhanced by increasing the molecular weight of the PRs from 20,000 to 100,000, which indicated that the increased effective range of αCD resulting from the higher molecular weight significantly affected the gel mechanical properties. A similar effect of molecular weight was reported for atelocollagen hydrogels post-crosslinked with carboxymethyl PRs [58]. Note that molecular weight exerted a stronger effect on the fracture stress and strain than coverage ratio in the previous studies.…”
Section: Tensile Testing Of Pratssupporting
confidence: 80%
“…To address this issue, PNAGAm-containing Ser-based reactive hydroxy groups, which allow post-crosslinking of the gel, were synthesized via the simple copolymerization of N-acryloyl glycinamide (NAGAm) and NASMe. Post-crosslinking of hydrogel materials is a useful strategy to tune their mechanical properties, particularly in biopolymer-based self-assembling systems [46,47].…”
Section: Preparation Of Hydrogels From Amino Acid-derived Vinyl Polymermentioning
confidence: 99%